Conservation implications of high genetic variation in two closely related and highly threatened species of Crambe (Brassicaceae) endemic to the island of Gran Canaria: C. tamadabensis and C. pritzelii. (21st July 2016) - Soto, Moisés E.; Marrero, Águedo; Roca‐Salinas, Alicia; Bramwell, David; Caujapé‐Castells, Juli
Abstract : We used data from 12 allozyme loci for two endemic Brassicaceae from Gran Canaria (the endangered narrow endemic Crambe tamadabensis and its more widespread congener C. pritzelii ) to assess whether their genetic diversity patterns reflect their phylogenetic closeness and contrasting population sizes and distribution areas, and to derive conservation implications. Genetic diversity values are high for both species and slightly higher in C. tamadabensis, despite its narrow distribution in north‐western Gran Canaria. At odds with the generally high interpopulation diversity levels reported in Canarian endemics, values of G ST in C. tamadabensis and C. pritzelii are rather low (0.067 and 0.126, respectively). We construe that the higher genetic structure detected in C. pritzelii is mainly a result of unbalanced allele frequencies and low population sizes at the edges of its distribution. The overall high allozyme variation detected in C. tamadabensis and C. pritzelii is nevertheless compatible with an incipient but consistent genetic differentiation between the two species, modulated by recurrent bottlenecks caused by grazing and drift. Our data suggest that conservation efforts aimed at maintaining the existing genetic connectivity in each species and ex situ conservation of seeds are the best strategies to conserve their genetic diversity.